(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The concept of truth is constantly developing on the basis of social and cultural factors, in various fields and as one of the main categories of human everyday consciousness, not only the conformity of human knowledge with objective reality, but also the ideal of a high level of knowledge, which is the basis for the development of modern science, and an effective way to achieve it. plays an important role in showing. From this point of view, information on the definition and formation of conceptual mechanisms in order to increase the essence of the concept of truth and its potential in human social life has been presented.